2023
DOI: 10.1101/2023.03.11.532204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of monoclonal antibody-based blocking ELISA for detecting SARS-CoV-2 exposure in animals

Abstract: The global pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses a significant threat to public health. Besides humans, SARS-CoV-2 can infect several animal species. Highly sensitive and specific diagnostic reagents and assays are urgently needed for rapid detection and implementation of strategies for prevention and control of the infection in animals. In this study, we initially developed a panel of monoclonal antibodies (mAbs) against SARS-CoV-2 nucleocapsid (N) protein. To detect S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…To evaluate the precision of the blocking biosensor assay for antibody detection, we tested a cohort of serum samples with known antibody statuses, which includes 86 known positive and 76 known negative samples from experimental cats. These samples were confirmed antibody statuses in our previous studies 29 . As shown in Figure 4A, receiver operating characteristic (ROC) analysis revealed that at PI value cut-off at 0.5877, the assay achieved a diagnostic sensitivity of 97.80% and a diagnostic specificity of 98.67%.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…To evaluate the precision of the blocking biosensor assay for antibody detection, we tested a cohort of serum samples with known antibody statuses, which includes 86 known positive and 76 known negative samples from experimental cats. These samples were confirmed antibody statuses in our previous studies 29 . As shown in Figure 4A, receiver operating characteristic (ROC) analysis revealed that at PI value cut-off at 0.5877, the assay achieved a diagnostic sensitivity of 97.80% and a diagnostic specificity of 98.67%.…”
Section: Resultssupporting
confidence: 90%
“…Purified protein was dialyzed using 1x phosphate-buffered saline (PBS) solution under 4℃ and then concentrated by polyethylene glycol 8000 (Thermo Fisher Scientific, 320 Waltham, MA). The SARS-CoV-2 N protein specific mAb #127-3 was generated in our previous study 6 .…”
Section: Preparation Of Antigen and Monoclonal Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…We suspected that there might be some possible transmissions between humans and cats during that period. Especially, the second seropositive peak could be related to human SARS-CoV-2 infections because about 14 days after being infected with SARS-CoV-2, the antibody level is detectable by our serological testing method [ 10 , 26 ], suggesting a possible human-to-cat transmission. However, we did not find any similarity between the positive case rates of human infections and cat seropositivity for the rest of the study period (between March 2022 and May 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A blocking enzyme-linked immunosorbent assay (bELISA) for detecting SARS-CoV-2 specific antibody response was developed and validated in-house. The detailed method was described in our previous publication [ 26 ]. All the serum samples collected from the cats were initially screened by bELISA.…”
Section: Methodsmentioning
confidence: 99%